Editorial: targeting aberrant hepatic inflammation for treatment of non‐alcoholic steatohepatitis. Issue 4 (28th January 2022) - Muthiah, Mark D.; Siddiqui, Mohammad S.
LINKED CONTENT: This article is linked to Safadi et al papers. To view these articles, visit https://doi.org/10.1111/apt.16664 and https://doi.org/10.1111/apt.16762